Dampak Globalisasi terhadap Nilai-Nilai Keislaman dalam Pendidikan Agama Islam - Adinda Zahrah; Putri, Deliana; Safira, Alya; Kholifah, Afiyatun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Globalization is a major phenomenon that brings rapid changes in the mindset, behavior, and culture of society, including students in formal educational settings. This condition presents significant challenges for Islamic Religious Education, which plays a crucial role in shaping character and internalizing Islamic values. This study aims to analyze how globalization influences students’ understanding, attitudes, and practices of Islamic values, as well as how Islamic Religious Education can respond adaptively to these changes. This research employs a qualitative approach using a literature study method that reviews books, scholarly articles, and relevant documents related to globalization, Islamic education, and character formation. Data were analyzed through processes of collection, classification, and interpretation to identify patterns of global influence on Islamic values. The findings reveal that globalization offers two major impacts: opportunities for the development of religious literacy through technological and informational access, and threats in the form of external values such as hedonism, individualism, and decreasing religious sensitivity. These findings highlight the need for educational strategies that balance the use of technology with the reinforcement of Islamic character, including the integration of Islamic values into digital-based learning, strengthening teacher role modeling, and habituating moral behavior within school activities. The implications of this study emphasize the importance of innovation in Islamic Religious Education to maintain the relevance of Islamic values amid the ongoing developments of globalization.